Forests and human health in the tropics: some important connections - Colfer, C.J.P.; Sheil, Douglas; Kaimowitz, D.; Kishi, M. (2006)
This paper contains an overview of the state of human health in and around forests, and the causal links between forests and human health. It identifies four central links between forests and human health, focusing on two central questions: 1. What are the human health conditions in and around forests? 2. What are the causal links between forests and human health? Finally, the article provides policy recommendations targeted to specific actors such as health professionals or foresters.